SELBSTBEWUBTSEIN: EIN PROBLEM DER PHILOSOPHIE NACH KANT. "ZUM VERHÄLTNIS REINHOLD-HÖLDERLINFICHTE" - Stolzenberg, Jürgen (Daimon Revista Internacional de Filosofia, 1994)
In this paper an attempt is made to elucidate the relationship between the different theories of self-consciousness of Karl Leonhard Reinhold, Friedrich Hölderlin and Johann Gottlieb Fichte. It is shown, that Reinhold was the first of the postkantian philosophers remarking a problem in the concept of self-consciousness and whose theory of consciousness and self-consciousness must be considered as teh theorical background of Hölderlin's Fichte-Critique in his famous paper on Judgement and Being from 1795. It is then shown, that there is an implicit answer of Fichte to Hölderlin's Critique in Fichte's System of Morals from 1798, where Fichte developed a new systematic interpretation of that concepts of self-consciousness, which Reinhold and Hölderlin had in view.